Service quality in multichannel services employing virtual channels - Sousa, Rui (2011)
Services employing virtual channels of delivery such as the Internet are typically multichannel. Service quality research in traditional services and, more recently, in e-services tends to take a single-channel perspective. This article argues that a multichannel setting introduces a set of complexities that call for a broader conceptualization of service quality, recognizing that customer experience is formed across all moments of contact with the firm through several channels. Building on existing research, the article develops a framework for conceptualizing multichannel service quality, distinguishing between virtual, physical, and integration quality. Integration quality is identified as a key new service quality component. The framework also addresses how the three components of service quality are delivered by the different parts of the service delivery system and identifies the associated challenges for providing good levels of service quality. A number of research and managerial implications as well as future research needs are put forward.